A case of thyroglossal duct cyst on the oral floor of a neonate. Issue 6 (November 2016) - Saito, Shion; Onidani, Kaoru; Yoshida, Shuji; Kamiyama, Isao; Ito, Aki; Tanaka, Jun-ichi
Abstract: Thyroglossal duct cysts are congenital cysts originating from thyroglossal duct remnants from the embryonic stage. Midline cervical cysts are the most common, while cysts in the oral cavity are rare. In the present report, we summarize our experience of a case of thyroglossal duct cyst in the oral floor in an 11-day-old infant; the cyst required enucleation because of feeding and respiratory difficulties in the infant. The patient presented with a protrusion in the oral floor at birth, and was admitted to the neonatal intensive care unit at our hospital at the age of 1 day because of being unable to feed orally. Based on the subsequent presentation of sleep apnoea, the patient underwent a detailed examination of the protrusion in the oral floor at our department where we performed enucleation of the cyst from the oral cavity at the age of 11 days. Following surgery, the patient exhibited functional suckling and the respiratory difficulties improved. To date, 1 year post-surgery, there has not been a recurrence of symptoms and progress is favourable.